The role of B lymphocytes in selected rheumatological and neurological diseases - Julia Zarańska; Arkadiusz Aab; Marta Miejska-Kamińska; Filip Kamiński; Adriana Liszka (Kazimierz Wielki University, 2023)
Introduction: B lymphocytes are responsible for humoral immune response. They play a crucial role in the development of the immune response and are essential in preventing infections as well as autoimmune and neoplastic diseases. They also constitute an important therapeutic target and are used in genetic and immunological therapies. In some cases, B cells can contribute to the pathogenesis of various diseases. Aim of study: The aim of this study is to summarize the current knowledge on the diverse role of B lymphocytes in selected rheumatic and neurological diseases using available scientific literature. Materials and Methods: This  review was conducted using  Pubmed and Google Scholar databases from 2009-2023. The research strategy was based on the following terms: B lymphocytes, monoclonal antibodies, myasthenia gravis, multiple sclerosis, systemic lupus erythematosus, systemic sclerosis, central nervous system damage, optic neuritis, Devic's syndrome. Conclusion: B lymphocytes play a significant role in the pathogenesis of many rheumatic and neurological diseases, therefore they represent a target for modern therapies. Their role and potential use are complex and differ depending on the specific disease entity. Further research will allow for the development of new targeted therapies, giving hope for improving the effectiveness of patient treatment.